REKONSTRUKSI KONSEP SIKLUS KEHIDUPAN MANUSIA DALAM PERSPEKTIF TEOLOGI PENDIDIKAN ISLAM - Akbar, Ghufran; Mulyadi; Raharjo, Harmanto; Izzuddin; Syafe'i, Isop (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
Classical Islamic education emphasizes the integration of knowledge, ethics, and spirituality, yet modern educational practices often face challenges such as value fragmentation, moral crises, and academic pragmatism. This study aims to describe the concepts of knowledge, teacher, and peer according to Burhanuddin Az Zarnuji in Ta‘līm al-Muta‘allim, analyze the ethical, epistemic, and socio-pedagogical values embedded in it, and explore the relevance of these ideas for contemporary Islamic education. A qualitative library research method with descriptive-analytical approach was employed. Data were collected from classical and contemporary literature, including Ta‘līm al-Muta‘allim, books on Islamic education, and indexed journal articles, and analyzed through content analysis to interpret educational concepts and values relevant to the modern context. The results indicate that Az Zarnuji regards knowledge as a spiritual light requiring sincerity, perseverance, and moral internalization. Teachers serve as mediators of knowledge and ethical role models, while peers and the learning environment support the development of student dispositions and character. Values such as sincerity, humility, discipline, and respect for teachers are shown to be relevant for cultivating holistic, humanistic, and contextual Islamic education. These findings have significant implications for curriculum design, character development, lifelong learning strategies, and reinforcing the integration of knowledge and ethics in modern Islamic education.